Critical Role of Alternative M2 Skewing in miR-155 Deletion-Mediated Protection of Colitis - Li, Jintao; Zhang, Ji; Guo, Hongxia; Yang, Shimin; Fan, Weiping; Ye, Nan; Tian, Zhiqiang; Yu, Tiantian; Ai, Guoping; Shen, Zigang; He, Haiyang; Yan, Ping; et al. (Frontiers in Immunology, 2018)
Inflammatory bowel disease (IBD) is associated with dysregulation of both innate and adaptive immune response in the intestine. MiR-155 is often expressed and functions in many immune cell types. Besides its function in adaptive immunity, miR-155 is a key regulator of the innate immune response in macrophages, dendritic cells, and even in epithelia cells. Although the roles of miR-155 within T and B lymphocytes in colitis have been reported, its function in innate immune cells has not been thoroughly examined. In this study, the dextran sulphate sodium (DSS)-induced colitis was established in wild-type (WT) and miR-155-/- mice. Our results showed that miR-155 deficiency in macrophages recapitulated the alleviated colitis feature of miR-155-/- mice and appeared to skew towards the alterative M2 phenotype. Notably, the predominance of M2 in colon can result in dampened intestinal immune cell proliferation and inhibit CD4 T cell polarization towards Th1 and Th17. Moreover, C/EBPβ and SOCS1 were demonstrated as two key functional targets in this process. We also provided evidence for use of miR-155 inhibitor to treat colitis. Collectively, the findings highlight the central role of alternative M2 skewing for miR-155 function in colitis and reveal that macrophages might be a main target for therapeutics.